Prevention of Melasma During Pregnancy: Risk Factors and Photoprotection-Focused Strategies - Zhao L; Fu X; Cheng H (Dove Medical Press, 2024)
Leilei Zhao,1 Xinmeng Fu,2 Hongbin Cheng3 1School of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan Province, People's Republic of China; 2Traditional Chinese Medicine Department, Boao Yiling Life Care Center, Qionghai, Hainan Province, People's Republic of China; 3Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan Province, People's Republic of ChinaCorrespondence: Hongbin Cheng, Email chenghongbin@cdutcm.edu.cnAbstract: Melasma is a benign but emotionally distressing skin condition that reduces patients' quality of life, with prevalence rates during pregnancy ranging from 36.4% to 75%. Troublingly, up to 30% of cases are reported to persist after delivery, even ten years later. And recurrence and aggravation are common in subsequent pregnancies. This review examines the risk factors and mechanisms associated with melasma during pregnancy and summarized corresponding preventive strategies. We emphasize the critical role of photoprotection, including the use of sunscreens from the first trimester, in reducing the incidence of melasma.Keywords: melasma, pregnancy, risk factors, prevention, photoprotection